The Cultivation of Intercultural Communication Competence Using Performed Culture Approach for English Majors in China - Jingjing, Zhou (Paradigm Academic Press Limited, 2025)
With the increasing frequency of intercultural exchanges, there is a significant rise in social demand for talents with intercultural communication competence (ICC) . However, due to their lack of experience in intercultural language teaching (ICLT), English major teachers in China struggle to effectively develop this core competence in students during their teaching. This issue causes students to easily develop misunderstandings and encounter communication barriers in intercultural interactions, thereby restricting the quality of talent cultivation for English majors. The Performed Culture Approach (PCA) is a new kind of ICLT approach that aims to cultivate students’ ICC. The aim of the present study is to explore the cultivation of ICC using PCA among English majors in China from the perspectives of both the students and teachers concerned. It was achieved by investigating students’ ICC level, comparing the perceived impact of PCA on ICC cultivation between teacher and student participants, and examining teachers’ intention to use PCA. The present study employs an interpretivist case study approach, utilizing the Three-dimensional Theory of ICC, the Context, Input, Process and Product (CIPP) evaluation model, and the Theory of Planned Behavior (TPB) as its theoretical framework. Data was drawn from individual interviews with eight teachers and 12 students, and was analyzed using the thematic analysis method. The findings reveal that students’ ICC is at a moderate level, showing an imbalance developmental pattern characterized as “knowledge-attitude-skill”. Both teachers and students affirm the positive impact of the PCA on ICC. PCA enhances students’ language proficiency, improves their intercultural behavior skills, and boosts students’ classroom participation and learning motivation. The learning facilitation factors of PCA include performance evaluation, performance activities, and pre-class tasks. However, there were notable variations in teachers’ intention to use PCA. Perceived behavioral control, attitude toward the behavior, subjective norm, and teachers’ cognition of ICLT influenced their intention to use PCA. Teachers’ intention to use PCA was determined by internal factors more than external factors. A cross-analysis of sub-cases from the perspectives of divergence and convergence yielded three themes: students’ developmental needs for ICC, the consistency between the PCA and students’ ICC developmental needs, and teachers’ ambivalence towards using PCA. An ICC cultivation model in the context of EFL in China was proposed based on students’ ICC development needs and facilitation factors of PCA. These findings have implications for policy and practice for the implementation of PCA in ICC cultivation among English majors in the EFL context of China.